2014
DOI: 10.7314/apjcp.2014.15.17.7159
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine for the Treatment of Patients with Osteosarcoma

Abstract: Background: Patients with recurrent or refractory osteosarcoma are considered to have a very poor prognosis, and new regimens are needed to improve the prognosis in this setting. Gemcitabine, a nucleoside antimetabolite, is an analog of deoxycytidine which mainly inhibits DNA synthesis through interfering with DNA chain elongation and depleting deoxynucleotide stores, resulting in gemcitabine-induced cell death. Here we performed a systemic analysis to evaluate gemcitabine based chemotherapy as salvage treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Gemcitabine-induced antitumor therapy resistance is a widely used model in studying chemotherapeutic resistance ( 6 ). Gemcitabine is used as a standard drug treatment for human osteosarcoma and has a significant therapeutic effect in osteosarcoma ( 7 ), however, the underlying mechanism requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine-induced antitumor therapy resistance is a widely used model in studying chemotherapeutic resistance ( 6 ). Gemcitabine is used as a standard drug treatment for human osteosarcoma and has a significant therapeutic effect in osteosarcoma ( 7 ), however, the underlying mechanism requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Type I collagen can also induce chemo‐resistant gene expression or activate signaling cascades, which possess detoxification capability. Gemcitabine, a nucleoside analog, is widely used in the treatment of human cancers 93‐95 . In PDAC, elevated level of type I collagen enhances gemcitabine resistance by increasing the expression of high mobility group A2 (HMGA2), 96,97 a nonhistone DNA‐binding nuclear protein involved in chromatin remodeling and gene transcription 98 .…”
Section: Mechanisms Of Type I Collagen Regulating Tumor Progressionmentioning
confidence: 99%
“…Gemcitabine is another drug that has recently made its way into clinical trials for OS, and so far, has shown promising results [21], but its true impact remains to be appreciated. The reasons why there has been little advancement in the field primarily relate to the highly aggressive and genetically unstable nature of OS, as well as the highly toxic features of chemotherapy.…”
Section: Medical Treatmentmentioning
confidence: 99%